An analysis of small dimensional fading wiretap lattice codes - Ducoat, Jérôme (2014)
We consider sums of inverse of algebraic norms as a code design criterion for fading wiretap channels. We study their behavior for small dimensional lattices built over the ring of integers of a number field, where the lattice points are taken from finite constellations, whose shaping is either cubic or spheric. Our analysis shows that unimodular lattices whose underlying number field has a small discriminant give the best performance so far.